Case Study at Bank Panin Dubai Syariah The Effects of Inflation, BI Rate, and Margin Rate on the Growth of Mudharabah Deposits - Tasya Virdausa; Dwi Retno Widiyanti; Sara Muthia Avicennayanti (Review of Islamic Economics and Finance, 2023)
Purpose – This study aims to examine how the inflation rate, BI rate, and margin rate affect the short- and long-term growth of mudharabah deposits at Panin Dubai Syariah Bank. Methodology - The analysis method that used is Error Correlation Model (ECM) by utilizing monthly data of 2019-2022 periods. Data acquired from BPS and financial reports published by OJK.  Findings - Inflation (X1), BI Rate (X2), and the profit- sharing rate (X3) were found to have a significant positive long-term effect on the growth of mudharabah deposits at Bank Panin Dubai Syariah. Meanwhile, the three have no effect on mudharabah deposit levels in the short term, either partially or simultaneously. The result of this study shows that the performance of Bank Panin Dubai Syariah as a finance institution in collecting public funds is stable in the short term, depending on the variables studied. But, in the long term, the bank is experiencing instability. Keywords: Islamic bank; margin; Inflation; Interest rate.